Organizational Commitment and Work Environment Towards the Performance of PNS Based on Values with Cultural: The Role of OCB - Muslimin, Irawan; Akob, Muh; Sumail, La Ode (International Business Management - Universitas Ciputra, 2024)
This study investigates the effect of organizational commitment and work environment on the performance of civil servants based on BerAKHLAK values at the BKD Office of South Sulawesi Province. The sampling technique used a sample of genus where all populations, as many as 127 respondents, were sampled, with data analysis using SEM-PLS. The results showed that organizational commitment has a positive and significant effect on the performance of civil servants based on values, but the work environment has no significant effect. Organizational commitment has a positive and significant effect on Organizational Citizenship Behavior (OCB), but the work environment has no significant effect. OCB has a positive and significant effect on the performance of civil servants based on values. Organizational commitment has a positive and significant effect on the performance of civil servants based on values through OCB. However, the work environment has no significant effect on the performance of civil servants based on values through OCB.